Flow Resistance Estimation Using the Empirical Chezy Method in Sediment-Laden Flow - Miskar Maini; Junita Eka Susanti (G-Tech: Jurnal Teknologi Terapan, 2025)
Hydraulic resistance, represented by the Chezy coefficient, is crucial in estimating flow discharge in open channels and serves as a fundamental parameter in designing hydraulic structures such as irrigation canals and river control facilities. This study investigates the behavior of the Chezy coefficient under non-sediment-laden (NSL) and sediment-laden (SL) flow conditions through controlled laboratory experiments using coarse sand, complemented by comparative analysis with data from irrigation channels and natural rivers. The results show that the ratio of mean velocity to shear velocity (U/u*) exhibits a robust correlation with discharge (Q) under both flow conditions, with a determination coefficient (R²) exceeding 0.96. The hydraulic radius (Rh) also shows a strong linear relationship with discharge (R ≈ 0.98), confirming its role in the empirical estimation of the Chezy coefficient (C). The value of C increases with higher velocity ratios but tends to be slightly lower under SL conditions due to increased resistance from suspended sediments. The Mean Absolute Error (MAE) value of 0.02 indicates a slight difference between NSL and SL conditions. These findings suggest that the empirical method is unreliable and exhibits significant differences in estimating Chezy under sediment-laden flow. It highlights the need for supplementary approaches to improve irrigation and river management design accuracy.